Islamic Education System in Welcoming the Era of Society 5.0 - Muhamad Uyun (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
The Industrial Revolution 4.0 to become Society 5.0 is a natural movement towards developing increasingly sophisticated information and technology. This study aims to propose a new construction in the field of Islamic education, namely the Islamic education system, to welcome the Era of Society 5.0. This research method is a literature survey combining previous references that follow the discussion. The findings of the researchers are that in welcoming the era of society 5.0, the education system fulfills three criteria for destructive thinking (innovation and creativity in learning), self-driving (hr professionals with a good mentality and open-mindedness, understanding situations quickly and accurately, honest and agile), and reshape or create (taking good experiences for better things).